Implementation of Sekolah Penggerak Programme to Address Chemistry Teachers Competency on Design PjBL-based Digital Teaching Materials in Padang - Suryani, Okta; Sari, Trisna Kumala; Riga, Riga; Mawardi, Mawardi; Putra, Ahadul (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Teaching materials for Sekolah Penggerak should be prepared based on a creative thinking learning model such as project-based learning (PjBL). However, based on the needs and situation of teachers towards the implementation of PjBL-based learning, implementation of PjBL in learning is still low, since the teachers in Padang need the advance training of preparation in PjBL learning material. The Community service activities have been carried out to provide experienced chemistry teachers in developing teaching materials based on Project-Based Learning. The implementation methods carried out in this activity are: (1) Analyzing the needs and situation of teachers towards the implementation of PjBL-based learning through questionnaires distributed, (2) Submission of material to service participants related to the PjBL learning model and syntax in this learning model explained by the speaker, then (3) Teachers are given the task of compiling and designing chemistry LKPDs using the PjBL model, (4) Teachers will present the results of the LKPD design compiled, and (5) evaluation of activities. The results of the service activities carried out can provide experience and understanding for chemistry teachers in Padang city regarding the PjBL learning model. Participants who attended this service activity could prepare chemistry teaching materials using the PjBL model so that teachers could be more innovative and creative. This activity service can provide motivation for teachers to prepare teaching materials in accordance with the demands of the Kurikulum Merdeka, especially in the implementation of project-based learning.